Peuplement benthique des grottes sous-marines de Sagres (Portugal, Atlantique nord-oriental). In: Biscoito, M., A.J. Almeida & P. Ré (Eds). A Tribute to Luiz Saldanha. - Boury-Esnault, N.; Harmelin, J.-G.; Ledoyer, M.; Saldanha, L.; Zibrowius, H. (Boletim do Museu Municipal do Funchal, 2001)
The benthic communities of 8 submarine caves from Sagres area (southern Portugal) have been surveyed by scuba diving (organismic and photographic sampling). These relatively shallow (vault: 10-16 m depth) and large (maximum length: 115 m) caves are subjected to relatively strong water circulation (waves, tides), except for some small more confined dark areas. As a result and with reference to Mediterranean caves, the community typically associated to dark, confined cavities is limited to those few calmer recesses despite the wide extension of darkness. Conversely, communities typical of shadyed and semidark parts expand widely inside the caves, together with some rheophylic invertebrates. Five physionomic zones have been distinguished in these caves. Species richness of sponges, scleractinians and bryozoans appears to be lower than in dark caves of the Mediterranean. The most interesting faunal traits of these caves are: (i) the occurrence of rich mixed populations of brachiopods (5 species) and of mysids (2 species) in remote parts; (ii) the occurrence of some species considered as Mediterranean endemics; (iii) the absence of some expected species (e.g. Corallium rubrum); (iv) the replacement of several Mediterranean species, highly diagnostic of cave environment, by vicariant sibling species, e.g. in the genera Aplysina (sponges), Puellina (bryozoans), Hemimysis (mysids).